Pharmacological correction of ulcerative colitis with dalargin - Andrei Yu. Liashev; Galina S. Mal’ (Research Results in Pharmacology)
Introduction: Ulcerative colitis is a chronic colonic disease with frequent relapses, affecting mainly people of active age. The effectiveness of existing treatment methods remains low. Dalargin has the following pharmacological effects: antioxidant, membrane-stabilizing and immunomodulatory, which are important in treating ulcerative colitis. The aim of the studywas to increase the effectiveness of pharmacological correction of ulcerative colitis with dalargin.